(untitled) (Research, Society and Development, 2022)
From the beginning, attention in relation to Covid-19 has drawn attention to the existence of risk groups, especially vulnerable to infection and it is known that, at the time of pregnancy, pregnancy changes are capable of making the woman susceptible, as well as previous comorbidities. Therefore, an integrative literature review was carried out, which sought to highlight the main complications resulting from SARS-CoV-2 infection during the gestational period. It has been found that physiological and immunological changes that accompany pregnancy can increase susceptibility to the newly emerging viral pathogen and the severity of the infection, such as fever and hypoxemia secondary to the acute hyperinflammatory stage of the disease, in addition to the presence of previous comorbidities such as hyperglycemia, heart disease, obesity, among others. In addition, in these cases, it is necessary to have an early diagnosis of the disease, adequate guidelines for the different levels of prevention, considering pregnant and postpartum women as a risk group for the development of severe or fatal forms, and, moreover, to maintain prenatal care. -sequential birth, as well as maintenance of gestational risk stratification at each appointment.